Results from Thailand's 2016 report card on physical activity for children and youth - Areekul Amornsriwatanakul (2018)
© 2016 Human Kinetics, Inc. Background: Physical activity (PA) is recognized as one of the core modifiable risk factors of noncommunicable diseases. However, little is known about PA in the Thai population, particularly in children. The report card (RC) project provided Thailand with an opportunity to assess PA behaviors in children. This paper summarizes the methodology, grading process, and the final grades of the Thai RC. Methods: A school-based survey was conducted to collect data from a nationally representative sample of children aged 6 to 17 years. Survey results provided the primary source for the RC. Nine indicators were graded using the Global Matrix 2.0 framework. Grading was undertaken by a national committee comprising experts from key stakeholders. Results: Grades ranged from F to B. Overall PA and Sedentary Behaviors both received the grade D-. Organized Sport Participation scored a C. Active Play scored the grade F. Active Transport and support from Family and Peers were both graded B. School, Community, and Government indicators were scored C. Conclusions: In Thai children, participation in PA and active play is very low; conversely, sedentary behaviors are high. These first data on patterns of activity for the Thailand RC will serve to guide national actions and advocacy aimed at increasing PA in children.